Conformisme et non-conformisme dans les Académies dissidentes, 1660-1860 - Françoise Deconinck-Brossard (Revue Française de Civilisation Britannique)
This article, based on new historiographical resources, shows that issues of orthodoxy and heresy played a crucial part in the life of Dissenting Academies, and that the line between conformity, conformism and non-conformism was not always as clear-cut as might be thought.